2000
DOI: 10.1007/s007050050052
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of the geonomic RNA of a mild strain of Japanese yam mosaic potyvirus

Abstract: We determined the complete nucleotide sequence of a mild strain of Japanese yam mosaic potyvirus (JYMV-M) and compared it with the published sequence of severe strain of JYMV (JYMV-J1). The genomic RNA of JYMV-M is 9,760 nucleotides (nts) in length, excluding the poly (A) tail, and encodes a polyprotein of 3,132 amino acids. Among nine potential cleavage sites, only the P1 and NIa recognition sites (between 6K1 and CI) had different sequences from those of JYMV-J1. The data confirm the strain status of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Analyses of the phylogenetic relationships were confined to the 30 sequences that did not show clear evidence of recombination, the nonrecombinant TuMV sequences. The homologous regions of the genomes of two isolates (J1 and Mild) of JYMV (Fuji & Nakamae 1999, 2000) were used as the outgroup for these analyses as blast searches had shown them to be the sequences in the international sequence databases most closely and consistently related to those of TuMV; their nucleotide sequences differed from those of TuMV by ≈ 15%; ranging from 10% to 23% in different parts of the genome. The genomic sequence of Scallion mosaic virus (Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the phylogenetic relationships were confined to the 30 sequences that did not show clear evidence of recombination, the nonrecombinant TuMV sequences. The homologous regions of the genomes of two isolates (J1 and Mild) of JYMV (Fuji & Nakamae 1999, 2000) were used as the outgroup for these analyses as blast searches had shown them to be the sequences in the international sequence databases most closely and consistently related to those of TuMV; their nucleotide sequences differed from those of TuMV by ≈ 15%; ranging from 10% to 23% in different parts of the genome. The genomic sequence of Scallion mosaic virus (Chen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Two genomic sequences of JYMV [10], [11], one of ScMV [12], and one of NYSV [13] were used as outgroups because BLAST searches had shown them to be most closely and consistently related to those of TuMV. TuMV Protein 1 (P1) genes were more closely related to those of JYMV than to those of ScMV, whereas for some intergenic regions between helper component-proteinase protein (HC-Pro) and nuclear inclusion b protein (NIb) the converse was true.…”
Section: Methodsmentioning
confidence: 99%
“…One of these is the ‘TuMV group’, which comprises TuMV and at least five other species, all from monocotyledonous plants. These include Japanese yam mosaic virus (JYMV) [10], [11], Narcissus yellow stripe virus (NYSV) [12], and Scallion mosaic virus (ScMV) [13], all known from full genomic sequences. Sequence analyses of the coat protein have shown that the TuMV group also contains Indian narcissus potyvirus and Narcissus late season yellows potyvirus.…”
Section: Introductionmentioning
confidence: 99%
“…The concats were used for evolutionary analyses. The corresponding regions of two sequences of Japanese yam mosaic virus (JYMV) (Fuji & Nakamae 1999, 2000), one of Scallion mosaic virus (ScMV) (Chen et al . 2002) and one of Narcissus yellow stripe virus (NYSV) (Chen et al .…”
Section: Methodsmentioning
confidence: 99%